Conformation Controls Mobility: 2H-Tetranaphthylporphyrins on Cu(111) - Kuliga, Jan; Massicot, Stephen; Adhikari, Rajan; Ruppel, Michael; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (ChemPhysChem, 2020)
The adsorption behavior and the mobility of 2H-Tetranaphthylporphyrin (2HTNP) on Cu(111) was investigated by scanning tunneling microscopy (STM) at room temperature (RT). The molecules adsorb, like the structurally related 2HTPP, in the "inverted" structure with the naphthyl plane restricted to an orientation parallel to the Cu surface. The orientation of the four naphthyl groups yields altogether 16 possible conformations. Due to the existence of rotamer pairs, 10 different appearances are expected on the surface, and all of them are identified by STM at RT. Most interestingly, the orientation of the naphthyl groups significantly influences the diffusion behavior of the molecules on Cu(111). We identify three different groups of conformers, which are either immobile, medium or fast diffusing at RT. The mobility seems to decrease with increasing size of the footprint of the conformers on the surface.
CRIS-Team WoS Importer:2020-03-03

Formation of highly ordered molecular porous 2D networks from cyano-functionalized porphyrins on Cu(111) - Steinrück, Hans-Peter; Adhikari, Rajan; Siglreithmaier, Gretel; Gurrath, Martin; Meusel, Manuel; Kuliga, Jan; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Marbach, Hubertus (Chemistry - A European Journal, 2020)
We investigated the adsorption of three related cyano-functionalized tetraphenyl porphyrin derivatives on Cu(111) by scanning tunneling microscopy (STM) in ultra-high vacuum (UHV) with the goal to identify the role of the cyano group and the central Cu atom for the intermolecular and supramolecular arrangement. The porphyrin derivatives studied were Cu-TCNPP, Cu-cisDCNPP, and 2H-cisDCNPP, that is, Cu-5,10,15,20-tetrakis-(p-cyano)-phenyl-porphyrin, Cu-meso-cis-di(p-cyano)-phenyl-porphyrin and 2H-meso-cis-di(p-cyano)-phenyl-porphyrin, respectively. Starting from different structures obtained after deposition at room temperature, all three molecules form the same long-range ordered hexagonal honeycomb-type structure with triangular pores and three molecules per unit cell. For the metal-free 2H-cisDCNPP, this occurs only after self-metalation upon heating. The structure-forming elements are pores with a distance of 3.1 nm, formed by triangles of porphyrins fused together by cyano-Cu-cyano interactions with Cu adatoms. This finding leads us to suggest that two cyano-phenyl groups in the "cis" position is the minimum prerequisite to form a highly ordered 2D porous molecular pattern. The experimental findings are supported by detailed density functional theory calculations to analyze the driving forces that lead to the formation of the porous hexagonal honeycomb-type structure.
CRIS-Team Scopus Importer:2020-07-03
Keywords: porphyrins coordinated networks cyano functionalization scanning tunneling microscopy (STM) density-functional theory (DFT) calculations

Metalation and coordination reactions of 2H-meso-trans-di(p-cyanophenyl) porphyrin on Ag(111) with coadsorbed cobalt atoms - Kuliga, Jan; Zhang, Liang; Lepper, Michael; Lungerich, Dominik; Hölzel, Helen; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2018)
We investigated the metalation and coordination reactions of Co with 2H-5,15-bis(para-cyanophenyl)10,20-bisphenylporphyrin (2HtransDCNPP) on a Ag(111) surface by scanning tunneling microscopy. At room temperature (RT), 2HtransDCNPPs self-assemble into a supramolecular structure stabilized by intermolecular hydrogen bonding. The metalation of 2HtransDCNPP is achieved either by depositing Co atoms onto the supramolecular structure at RT, or, alternatively, by depositing the molecules onto a submonolayer Co-precovered Ag(111) surface with a subsequent heating to 500 K. In addition, the molecules coordinate to Co atoms through the N atoms in the peripheral cyano groups with a preference of isolated 4-fold coordination motifs at RT.

Metalation of 2HTCNPP on Ag(111) with Zn: Evidence for the Sitting atop Complex at Room Temperature - Kuliga, Jan; De Campos Ferreirra, Rodrigo Cezar; Adhikari, Rajan; Massicot, Stephen; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Marbach, Hubertus; De Siervo, Abner; Steinrück, Hans-Peter (ChemPhysChem, 2021)
We study the interaction and metalation reaction of a free base 5,10,15,20-terakis(4-cyanophenyl)porphyrin (2HTCNPP) with post-deposited Zn atoms and the targeted reaction product Zn-5,10,15,20-terakis(4-cyanophenyl)porphyrin (ZnTCNPP) on a Ag(111) surface. The investigations are performed with scanning tunneling microscopy at room temperature after Zn deposition and subsequent heating. The goal is to obtain further insights in the metalation reaction and the influence of the cyanogroups on this reaction. The interaction of 2HTCNPP with post-deposited Zn leads to the formation of three different 2D ordered island types that coexist on the surface. All contain a new species with a bright appearance, which increases with the amount of post-deposited Zn. We attribute this to metastable SAT ("sitting atop") complexes formed by Zn and the macrocycle, that is, an intermediate in the metalation reaction to ZnTCNPP, which occurs upon heating to 500 K. Interestingly, the activation barrier for the successive reaction of the SAT complex to the metalated ZnTCNPP species can also be overcome by a voltage pulse applied to the STM tip.
CRIS-Team WoS Importer:2021-01-29

On the adsorption of different tetranaphthylporphyrins on Cu(111) and Ag(111) - Brox, Jan; Adhikari, Rajan; Shaker, Majid; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Jaekel, Simon; Steinrück, Hans-Peter (Surface Science, 2022)
We address the adsorption of 2H-tetranaphthylporphyrin (2HTNP) and 2H-tetranaphthylbenzoporphyrin (2HTNBP) on Cu(111) and Ag(111). The difference between the two molecules is that for 2HTNBP the pyrrole groups are replaced by isoindole groups. We were interested in the resulting differences in the adsorption behavior on the two surfaces, in particular the role of the naphthyl groups. The investigations are performed with scanning tunneling microscopy at room temperature (RT) and after heating treatments (500 and 600 K). On Ag(111), 2HTNP forms a commensurable superstructure at RT, which transforms to a denser packed, non-commensurable structure upon annealing. For 2HTNBP, individual molecules are observed on Cu(111) at RT, which exhibit different mobility. In contrast, on Ag(111) the formation of ordered 2HTNBP islands occurs, which are stabilized by T-type interactions. After heating to 500 K, these islands undergo a structural change to a denser packed structure, which is stabilized by π-π stacking of neighboring naphthyl groups.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Commensurability; Naphthyl functionalization; Porphyrins; Self-assembly; STM

Self-Assembled 2D-Coordination Kagome, Quadratic, and Close-Packed Hexagonal Lattices Formed from a Cyano-Functionalized Benzoporphyrin on Cu(111) - Adhikari, Rajan; Kuliga, Jan; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2021)
We investigated the adsorption of 2H-5,10,15,20-Tetracyanophenyl-Tetrabenzoporphyrin (2H-TCNPTBP) molecules on Cu(111) by scanning tunneling microscopy in ultrahigh vacuum at room temperature. Three types of network structures are observed to coexist on the surface. The first two, a porous Kagome lattice and a porous quadratic structure, are stabilized by cyano-Cu-cyano bonds with Cu adatoms; the third is a close-packed hexagonal network, with much weaker intermolecular H-bonds and dipole-dipole interactions of oppositely oriented cyano end groups. The coexistence of the three structures is attributed to very similar energetics. While the two metal-coordinated porous structures with identical molecular density are stabilized by the energy gain due to the network formation, the hexagonal network compensates the weaker intermolecular interactions by a factor of 2.3 higher molecular density; furthermore, kinetic stabilization might play a role. Our results show that cyano functionalization of benzoporphyrins gives rise to unusual two-dimensional self-Assembled lattice structures.
CRIS-Team Scopus Importer:2021-05-14

Structure and Conformation of Individual Molecules upon Adsorption of a Mixture of Benzoporphyrins on Ag(111), Cu(111), and Cu(110) Surfaces - Adhikari, Rajan; Brox, Jan; Massicot, Stephen; Ruppel, Michael; Jux, Norbert; Marbach, Hubertus; Steinrück, Hans-Peter (ChemPhysChem, 2023)
We investigated the adsorption behavior of a mixture of six 2H-tetrakis-(3, 5-di-tert-butylphenyl)(x)benzoporphyrins (2H-diTTBP(x)BPs, x=0, 1, 2-cis, 2-trans, 3, and 4) on Ag(111), Cu(111) and Cu(110) at room temperature by scanning tunneling microscopy (STM) under ultra-high vacuum conditions. On Ag(111), we observe an ordered two-dimensional square phase, which is stable up to 400 K. On Cu(111), the same square phase coexists with a stripe phase, which disappears at 400 K. In contrast, on Cu(110), 2H-diTTBP(x)BPs adsorb as immobile isolated molecules or dispersed short chains along the [1 (Formula presented.) 0] substrate direction, which remain intact up to 450 K. The stabilization of the 2D supramolecular structures on Ag(111) and Cu(111), and of the 1D short chains on Cu(110) is attributed to van der Waals interactions between the tert-butyl and phenyl groups of neighboring molecules. From high-resolution STM, we can assign all six 2H-diTTBP(x)BPs within the ordered structures. Moreover, we deduce a crown shape quadratic conformation on Ag(111) and Cu(111), an additional saddle-shape on Cu(111), and an inverted structure and a quadratic appearance on Cu(110). The different conformations are attributed to the different degree of interaction of the iminic nitrogen atoms of the isoindole and pyrrole groups with the substrate atoms.
CRIS-Team Scopus Importer:2023-07-21
Keywords: 2H-diTTBP(x)BPs; benzoporphyrin; isoindole groups; scanning tunneling microscopy; self-assembly